Lost to the Sea: Predicted Climate Change Threats to Saltwater Crocodile Nesting Habitat - Fukuda, Yusuke; McDonald, Peter J.; Crase, Beth (Frontiers in Ecology and Evolution, 2022)
Climate change is predicted to have devastating impacts on apex predators such as eliminating their required habitats. Crocodilians are no exception as most species require freshwater for nesting, and such freshwater habitats are particularly vulnerable to saltwater inundation (SWI) caused by the sea level rise (SLR) from global warming. Here, we examined the impacts of climate change on saltwater crocodiles Crocodylus porosus in terms of the potential loss of nesting habitat in the Northern Territory, Australia; an area that contains the world’s most extensive nesting habitat for the species. Our spatial model, derived from 730 nest locations and selected environmental features, estimated a total of 32,306.91km2 of current suitable habitat across the study region. The most important variable was distance to perennial lakes (71.0% contribution, 87.5% permutation importance), which is negatively correlated with nesting habitat suitability. We found that projected changes in temperature and rainfall by 2100 could impact the area of suitable nesting habitat negatively or positively (0.33% decrease under low future emission climate scenario, and 32.30% increase under high emission scenario). Nevertheless, this can be cancelled by the strong negative impact of SLR and concomitant SWI on nesting areas. A portion (16.40%) of the modelled suitable habitat for a subsection of our study area, the Kakadu Region, were already subject to >0.25 m SWI in 2013. The suitable area for nesting in this region is predicted to be further reduced to 1775.70 km2 with 1.1 m SLR predicted for 2100, representing 49.81% loss between 2013-2100. Although the estimates of habitat loss do not account for the potential creation of new habitat, nor for the uncertainty in the degree of future SLR, our results suggest that SLR driven by continuing global warming can be the major threat to mound-nest-building crocodilians including C. porosus, rather than direct impacts from changes in temperature and rainfall. The degree of impact on saltwater crocodiles will be determined by the interplay between the loss of nesting habitat, which would appear inevitable under current global warming, and the ability to expand into new areas created by the expansion of the tropics.